VARIETAL RESPONSE OF OKRA ( AL RESPONSE OF OKRA (Abelmoschus esulentus Abelmoschus esulentus L. MOENCH) TO GA3 APPLICATION UNDER WALK IN TUNNEL GREENHOUSE IN COLD DESERTS - M. S. KANWAR; P. ISHFAQ AKBAR (The Bioscan, 2019)
Response of different varieties of okra to the application of gibberellic acid as seed treatment was studied in Factorial RBD in three replications. Results revealed that varieties have significant effect on all the plant characters except fruit length, fruit diameter and harvest duration. Gibberellic acid treatment was found to be non-significant for most of the characters except days to germination, number of ridges and days to harvest. Interactions of variety and gibberellic acid were non-significant for yield, fruit diameter and harvest duration only. Gibberellic acid (40 ppm) was best for early seed germination of okra. Pusa Sawni recorded highest number of fruits per plant (6.84), yield per plant (60.27 gm) and yield per ha.(402 Q). It may be concluded that Pusa Sawni is a good choice for early and total yield. Seed treatment with gibberellic acid in the concentrations of 40 ppm and 70 ppm is beneficial for seed germination and yield, respectively.